Effect of machining parameters on the surface finish quality of natural fiber composites - Too, Mei Xian (Universiti Sains Malaysia, 2019)
In recent years, natural fiber reinforced composites are getting greater attentions among manufacturers due to its advantages of environmentally friendly, low cost and wide range of available renewable resources in nature. Natural fiber reinforced composite (NFRC) is a composite material that consists of a matrix embedded with natural fibers such as banana, kenaf, sisal and so on, while the fiber reinforced composite (FRC) is consists of manmade or synthetic fibers and a matrix. In this research, the type of natural fiber reinforced composites used is kenaf fiber reinforced polyester composites (KFRP) to study the effect of machining parameters on its surface finish quality. Polyester is a kind of thermoplastics which will not deformed thermally under high temperature as highly cross-linked structure in between each molecule, thus it gives good properties to the material, for example, good strength. Turning operation without cutting fluids were carried out with different cutting speed and feed rate settings on KFRP specimens for two times with depth of cut of 0.5 mm. After that, the surface finish quality of the composite specimen were measured using machine vision method by processing the images of composite specimens with angle of rotations, 0°, 90°, 180° and 270°. With the analysis of all the results of the surface roughness of all composite specimens, it can conclude that medium cutting speed and medium feed rate lead to the better surface finish quality. However, the non-homogenous properties of composite makes difficult to predict the surface finish quality in the subsequent turning.